Evaluation of Land Suitability for Coconut Plants in Airmadidi District, North Minahasa Regency, North Sulawesi - Aditya Dyah Utami; Panji Romadhon; Rahadian Adi Prasetyo; Heri Setyawan (Warmadewa University Press, 2024)
Airmadidi District is one of the coconut producing areas in North Minahasa Regency. Coconut plants are important for the community because each part has economic value. The purpose of the study was to identify the actual and potential land suitability classes for coconut plants in Airmadidi District. The research method used was the survey method. Determination of land suitability classes used a matching method between land characteristics and land suitability criteria. The results showed that the actual land suitability class in the Airmadidi District land unit was quite suitable (S2) and marginally suitable (S3) with limiting factors of water availability (wa) in the form of rainfall, nutrient retention (nr) in the form of Soil CEC and nutrient availability (na) in the form of N-Total, P2O5 and K2O. The potential land suitability class in the Airmadidi District land unit was very suitable (S1) and quite suitable (2) with limiting factors of available nutrients (na) in the form of N-Total, P2O5 and K2O.